2021
DOI: 10.1101/2021.12.06.471432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graded Variation In Cortical T1w/T2w Myelination During Adolescence

Abstract: Myelination influences brain connectivity during sensitive periods of development by enhancing neural signaling speed and regulating synapse formation to reduce plasticity. However, in vivo studies characterizing the maturational timing of cortical myelination during human development remain scant. Here, we take advantage of recent advances in high-resolution cortical T1w/T2w myelin mapping methods, including principled correction of B1+ transmit field effects, using data from the Human Connectome Project in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…So, to put it crudely, one would expect that more myelin equals more ability. At the same time, previous research indicates that myelination is not a linear process throughout the life span but rather that it proceeds in waves and that different regions follow different timelines [15,52,54]. Since the current sample is constrained with respect to the included ages, one could argue that such a snapshot of development should lend itself especially well to revealing correlations with behavior.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…So, to put it crudely, one would expect that more myelin equals more ability. At the same time, previous research indicates that myelination is not a linear process throughout the life span but rather that it proceeds in waves and that different regions follow different timelines [15,52,54]. Since the current sample is constrained with respect to the included ages, one could argue that such a snapshot of development should lend itself especially well to revealing correlations with behavior.…”
Section: Discussionmentioning
confidence: 97%
“…The literature suggests that primary sensory cortices are myelinated earlier than higher-order cortical and limbic areas and the insular cortices [51][52][53][54]. In addition, when investigating a cross-sectional sample spanning almost eight decades, Grydeland et al [52] showed that the age at peak myelination was bimodally distributed, with primary sensory areas reaching their highest point before puberty, while associative cortical areas did not reach theirs until after puberty.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being more accurate neuroanatomical representations of the relative differences in myelin content across the cerebral cortex, the transmit field corrected group average maps for each species can be used as reference template maps for future studies’ B1+ corrections of T1w/T2w myelin maps in individuals. Such B1+ corrected T1w/T2w myelin maps are now appropriate for more detailed studies of inter-participant differences with regard to behavior, development, aging, and disease, as well as cross-species differences, some of which will be presented elsewhere (Baum et al, 2021). Importantly, T1w/T2w ratio values are interpretable only as relative differences in a consistently acquired study protocol, and any comparisons across studies would require some kind of harmonization approach.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in this work we focus exclusively on the effects of bias and nuisance from spurious B1+ variations on the T1w/T2w myelin maps used in these linear regressions and not on any neuroscientific questions of interest. Such neuroscientific questions will be properly addressed in subsequent publications using more advanced statistical models (e.g., Baum et al, 2021 for development). For this reason, we do not assess the statistical significance of these effects and will comment on them only qualitatively insofar as it is useful to describe the effects of the transmit field correction.…”
Section: Methodsmentioning
confidence: 99%
“…Cortical myelination is a crucial feature of postnatal brain development, allowing for efficient signal transmission and structural support (Bartzokis, 2012;Baumann & Pham-Dinh, 2001;Liu et al, 2019;Waxman & Bennett, 1972). Several studies substantiate the utility of T1w/T2w ratio for mapping global and regional cortical maturational patterns (Baum et al, 2021;Grydeland et al, 2013Grydeland et al, , 2019Shafee et al, 2015), with ratios being positively associated with age across childhood and adolescence, as well as for assessing associations with cognitive performance in youth (Grydeland et al, 2013;Vandewouw et al, 2019).…”
Section: Introductionmentioning
confidence: 99%